2019
DOI: 10.2478/eb-2019-0008
|View full text |Cite
|
Sign up to set email alerts
|

External Debt Financing and Public Capital Investment in Nigeria: A Critical Evaluation

Abstract: This study considers the consequences of external loan on capital investment in Nigeria. Data for the study have been collected from the World Bank and Central Bank of Nigeria Statistical Bulletin, 2018 edition. The variables on which data are sourced include government capital expenditure, external debt accumulation, debt servicing cost, inflation rate, and exchange rate. Government capital expenditure is the dependent variable, while external debt accumulation and debt servicing cost are the key independent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…In addition, Nwafor, Odey & Effiong (2017) found domestic savings to be insensitive to financial liberalization in Nigeria for the period under study. Apart from some flaws of CAL as itemized earlier, Omodero (2019) in her study found that accumulation of external debt which was one of the upshots of liberalization imposed an adverse effect on capital investment in Nigeria. From the mixed outcome angle, private investments appeared to react differently to financial or capital openness in the short run and the long run.…”
Section: Literature Reviewmentioning
confidence: 76%
“…In addition, Nwafor, Odey & Effiong (2017) found domestic savings to be insensitive to financial liberalization in Nigeria for the period under study. Apart from some flaws of CAL as itemized earlier, Omodero (2019) in her study found that accumulation of external debt which was one of the upshots of liberalization imposed an adverse effect on capital investment in Nigeria. From the mixed outcome angle, private investments appeared to react differently to financial or capital openness in the short run and the long run.…”
Section: Literature Reviewmentioning
confidence: 76%
“…At country-specific level, researchers have also assessed the impact of public debt on public expenditure, particularly in developing countries such as Bangladesh, Kenya, Namibia, Nigeria, South Africa, including Uganda, and found that public debt (stock, servicing) is positively related to aggregate and/or components of public expenditure (Abu et al, 2022;Ahaisibwe, 2018;Fagge & Ibrahim, 2018;Firoj et al, 2018;Iiyambo & Kaulihowa, 2020;Kiminyei, 2014Kiminyei, , 2019Ncanywa & Masoga, 2018;Omodero, 2019;Ukwueze, 2015). On the contrary, some authors discovered that public debt (stock and servicing) decelerates public expenditure (Adamu, 2016;Aregbeyen & Akpan, 2013).…”
Section: Review Of Literature On Public Expenditure and Debt Relation...mentioning
confidence: 99%
“…It was found that debt overhang and debt burden in Nigeria were due to the usage of borrowed funds into unproductive activities such as payment of salaries and allowances, which had hindered economic growth. Omodero (2019) emphasised the consequences of external loans in Nigeria between 1996 and 2018. Using the regression technique to analyse the data, it was revealed that external loans had a significant and negative impact on capital investment, while the cost of external debt exerted a positive and statistically significant impact on capital investment.…”
Section: Nigerian Studiesmentioning
confidence: 99%